Optimation of a Table Conveyor Type Grading Machine to Increase the Performance of Green Coffee Manual Sortation - Sukrisno Widyotomo (Indonesian Coffee and Cocoa Research Institute, 2006)
Coffee consumers request a good quality of green coffee to get a good coffee cup taste. Defective beans e.g. black bean, brown bean and broken bean are associated to low coffee quality which give negative effects to final taste. To meet the standard export requirement, coffee beans have to be graded before being traded. Until now, grading process is generally carried out manually. The method gives better product, so the grading cost is very expensive about 40% of total processing cost. Meanwhile, shortage of skill workers is a limiting factor of the process. Therefore, improving the manual sorting by providing machine for grading of green coffee is good alternative to reduce the grading cost. Indonesian Coffee and Cocoa Research Institute has designed a table conveyor type grading machine in order to improve the performance of the manual grading productivity and consistent quality and to reduce the grading cost. The conveyor belt has a dimension of 5700 mm of length, 610 mm of width and 6 mm of thickness. The rotating of belt conveyor powered by an electro motor 3 HP, 3 phase and 1420 rpm. The result showed that the optimum capacity of grading machine was 390 kg/hour reached when the speed 16 rpm and 3 kg/m 2 of green beans on belt conveyor with productivity 1870 kg/man-day compared to the productivity full manually process 743 kg/man-day. Percentage of product in outlet 1 was 4.2% as broken beans, 0.26% as brown beans, 0.68% as one hole in beans and 0.61% as more than one hole in beans. Percentage of product in outlet 2 was 39.54% as broken beans, 4.23% as brown beans 7.19% as black beans, 4.47% as one hole in beans and 4.43% as more than one hole in beans. Cost of grading process per kg of green coffee is Rp20,-. Key words : Coffee, Grading, Conveyor table, Quality